The Effect of Health Education on the Knowledge of Class XI Adolescent Girls About Dysmenorrhea at SMAN 2 Cimalaka Sumedang Regency - Tresna Komalasari; Velia Bernica (Jurnal EduHealth, 2024)
Menstruation is the process of blood discharge from the uterus that occurs due to the shedding of the inner uterine wall which contains many blood vessels and unfertilized eggs, Dysmenorrhea is abdominal pain in the lower part that generally occurs before or during menstruation. This study aims to determine the effect of Health Education on dysmenorrhea. The type of research used is pre-experiment with one group pretest-posttest design. The sample in this study is all grade XI young women at SMAN 2 Cimalaka, Sumedang Regency in 2024 A total of 88 people (total sampling) will be held on April 26, 2024 at the Hall of SMAN 2 Cimalaka. Univariate analysis uses a central tendency distribution and bivariate analysis uses paired t-tests. The results showed that the average knowledge of adolescent girls about dysmenorrhea before Health Education was 57.70 and after Health Education was 92.16. Providing Health Education is one of the efforts to increase knowledge both using electronic media and social media. There is an influence of Health Education on the knowledge of grade XI adolescent girls about dysmenorrhea at SMAN 2 Cimalaka, Sumedang Regency in 2024 with a value of ρ= 0.000 or α<0.05. As for suggestions for respondents to be more active in seeking health information both from social media, electronics and so on to add insight and know how to handle dysmenorrhea, for educational institutions and health workers need to work together to hold health education activities regarding dysmenorrhea